STRATEGY TO ACHIEVE FINANCIAL GOALS (Descriptive Study on University of Brawijaya Student) - Megaputra, Gigih; Indrawati, Nur Khusniyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Financial problems often occurs particularly to college student whose doesn’t live with their parents anymore (board). This college student usually receive allowance each month from their parents. Generally, the acceptance period once a month potentially cause error in consumption patterns if there is no planning and financial discipline in spending. To be able to avoid the financial problems everyone needs to learn personal financial planning. The main objective of this research paper is to reveal and understand the students’ strategies to achieve their personal financial goals. The research setting are the canteens at Brawijaya University. This study uses descriptive qualitative research. The data uses in this study is primary data, which obtained by observation at the study site and depth interviews to the students of Brawijaya University. The result show that the strategy to achieve student financial goal is determined by application of appropiate plan of actions with the personal financial situation and goals, this plan of actions are to maintain or expand the current sitation or perform a new innovation to create something new. The implication of this research is personal financial planning is expected to be reference for students to achieve their financial goals. Preparation and application of personal financial planning is intended to facilitate the avhievement of students’ personal financial goals. The purpose of financial planning is not just a set routine of income and expenses, but also can be used to achieve financial goals that are specific. Keywords: Personal Financial Planning, Personal Financial Goals, Personal Financial Situation.